The Effect of Accounting Earnings and Company Size on Abnormal Stock Returns in Food and Beverage Sub-Sector Manufacturing Companies - Asri, Marselinus (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study evaluates the simultaneous effect of accounting earnings and company size on abnormal stock returns in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange. The hypothesis tested is that accounting earnings have a positive influence on abnormal returns, while company size also has a positive influence on abnormal returns. This study uses a quantitative approach with multiple linear regression analysis to evaluate data from 41 companies selected using purposive sampling. The data used includes financial statements for 2018-2022, with the main variables being accounting earnings, company size, and abnormal return. The research findings show that accounting earnings has a negative and significant effect on abnormal returns, while company size has a positive and significant impact. This indicates that companies with higher net income tend to have lower abnormal returns, while companies with larger sizes have higher abnormal returns. Discussion of the results suggests that investors may view high accounting earnings skeptically, while firm size provides a positive signal of stability and operational capacity. The implications of this study include the importance of corporate managers considering how accounting earnings and firm size simultaneously affect stock performance in strategic decision-making. In addition, this research opens up opportunities for further studies that examine the interaction of other financial variables on abnormal returns. Future studies are recommended to use longitudinal data and qualitative approaches to deepen the understanding of the dynamics of stock performance.